Measurement and Analysis of the Relationship between General Revenues and Imbalance in Iraq’s Export Structure For duration (2004-2021) - Muhammad Abdel Ghani *, Saja; Jabr Ashoor , Ehsan (Journal of Economics and Administrative Sciences, 2024)
The Iraqi economy relies primarily on oil exports to achieve necessary financial surpluses in order to finance economic and social development plans. Capital imports also contribute to improving the productive capacity of all sectors that directly or indirectly contribute to the country’s economic growth if they actually exist. These imports, represented by the equipment and machinery necessary for building and developing infrastructure in Iraq, which cannot be provided except through foreign trade, make Iraq closely connected to broad economic relationships with most of the developed world economies. Oil revenues have had a positive impact on the general budget situation. However, on the other hand, the lack of a productive base has led to the leakage of revenues towards imports to meet domestic demand, resulting in an imbalance in the overall export structure. Moreover the research objective was to identify the relative importance of total exports in Iraq and how they are affected by oil revenues during the period 2004-2021. The hypothesis is fiscal policy has led to a disruption in the structure of Iraq’s exports. And one of the most important result that appeared general revenues depend to a large extent on oil revenues compared to other revenues (non-oil), which means that the Iraqi economy is considered one-sided. With the weakness of revenues achieved from productive sectors (industry and agriculture) as well as weak tax revenues, this leads to an imbalance in the structure of the trade balance, evident through the dominance of oil exports over total exports in the country. Paper type: Research paper.